2008
DOI: 10.1136/gut.2007.145839
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of T cell response and bacterial clearance in human volunteers challenged with Helicobacter pylori revealed by randomised controlled vaccination with Ty21a-based Salmonella vaccines

Abstract: Background:Helicobacter pylori remains a global health hazard, and vaccination would be ideal for its control. Natural infection appears not to induce protective immunity. Thus, the feasibility of a vaccine for humans is doubtful.Methods:In two prospective, randomised, double-blind, controlled studies (Paul Ehrlich Institute application nos 0802/02 and 1097/01), live vaccines against H pylori were tested in human volunteers seronegative for, and without evidence of, active H pylori infection. Volunteers (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 43 publications
3
94
1
5
Order By: Relevance
“…The finding that control mice vaccinated with the S. Typhimurium 'carrier' also exhibit reductions in H. pylori numbers is consistent with previous reports from studies in both mice and humans [16,24,32]. While vaccinating with the carrier alone had some protective effect, it was seldom as effective as vaccination with H. pylori-specific antigen, which consistently results in a further 1 log reduction in bacterial numbers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding that control mice vaccinated with the S. Typhimurium 'carrier' also exhibit reductions in H. pylori numbers is consistent with previous reports from studies in both mice and humans [16,24,32]. While vaccinating with the carrier alone had some protective effect, it was seldom as effective as vaccination with H. pylori-specific antigen, which consistently results in a further 1 log reduction in bacterial numbers.…”
Section: Discussionsupporting
confidence: 90%
“…This observation has also been supported by data from a recent trial of a recombinant attenuated Salmonella enterica serovar Typhi (S. Typhi)-based H. pylori vaccine in human volunteers. In this study, healthy (H. pylori negative) adult volunteers were vaccinated orally with recombinant S. Typhi expressing H. pylori antigen, and later challenged with a well-characterised H. pylori strain [16]. Vaccine-specific CD4 1 T-cell responses were detected and found to correlate with reductions in colonisation in some vaccinated volunteers.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The corresponding mutation rate of 7.5 Â 10 À 6 , which is similar to that during chronic infection, implies the lack of an inflammatory response in this patient for reasons that are currently unknown, but possibly involved a low number of 10 5 colony-forming units (c.f.u.) in the inoculum 32 in comparison with 10 9 c.f.u. in this re-infection study and to 7.5 Â 10 8 c.f.u.…”
Section: Discussionmentioning
confidence: 99%
“…Several vaccination regimens induce protective immunity in animal models; these include subunit vaccines containing H. pylori urease (8), neutrophil-activating protein (9), or adhesin A (10), but also recombinant live Salmonella vaccines expressing Helicobacter Ags (11). Clinical trials have demonstrated the immunogenicity of experimental vaccines in human volunteers (12)(13)(14). However, all current vaccine development efforts are hampered by their failure to achieve sterilizing immunity in rodent models, let alone in humans.…”
Section: P Ersistent Gastric Infection With the Bacterial Pathogenmentioning
confidence: 99%